A rare case of scrub typhus with complete heart block - Sharmili Sinha; Jyotirmaya Pati; Brajaraj Das (Apollo Medicine)
Scrub typhus is a tropical fever prevalent in South East Asia. It is a multisystem disease which can vary widely in clinical manifestations from mild generalized symptoms to multiorgan dysfunction syndrome. Myocarditis is a known complication which can present with tachycardia, heart failure, and very rarely heart blocks. We report a case of complete heart block due to scrub typhus case which was treated successfully at our center.